BELANJA MODAL KABUPATEN/KOTA DI PROVINSI LAMPUNG: AMATAN TERHADAP PENDAPATAN DAERAH DAN DANA PERIMBANGAN - Wardhana, Sania Adelina; Sari, Shinta Permata (Media Mahardhika, 2024)
Lampung is a province in Indonesia with the highest percentage of regional budget realization for the 2022 fiscal year. However, the Lampung Provincial Budget's allocation for capital expenditure remains inadequate when compared to the realization of operational expenditure. When regional expenditure is viewed in terms of benefits, allocating the budget to the capital sector is very beneficial and productive for growth and service provision to the community. This study aims to analyze the effect of Regional Original Revenue, General Allocation Fund, Special Allocation Fund and Profit Sharing Fund on District/City Capital Expenditure in Lampung Province for 2019-2022. This study determined a sample of 15 administrative regions in Lampung Province covering 13 districts and 2 cities using a quantitative approach. The data used is secondary data in the form of time series data for the 2019-2022 fiscal year period sourced from the website of the Central Statistics Agency of Lampung Province and the Directorate General of Financial Balance of the Ministry of Finance of the Republic of Indonesia in the form of a Report on the Realization of the District/City Budget of Lampung Province. Multiple Linear Regression Analysis is used to test hypotheses in data analysis techniques that prove Local Original Revenue and Special Allocation Fund have an effect on Capital Expenditure. Meanwhile, the General Allocation Fund and Profit Sharing Fund have no effect on capital expenditure.